Assessment of oxygenation after balloon pulmonary angioplasty for patients with inoperable chronic thromboembolic pulmonary hypertension. (15th June 2021) - Matsuoka, Yoichiro; Taniguchi, Yu; Miwa, Keisuke; Sumimoto, Keiko; Tsuboi, Yasunori; Onishi, Hiroyuki; Yanaka, Kenichi; Emoto, Noriaki; Hirata, Kenichi
Abstract: Background: The efficacy of balloon pulmonary angioplasty (BPA) in patients with inoperable chronic thromboembolic pulmonary hypertension would be promising. However, some patients showed residual dyspnea or symptoms, despite normalized hemodynamics. We aimed to clarify the clinical impact of oxygenation parameters on BPA outcome. Method: Ninety-nine consecutive patients who underwent BPA from September 2011 to December 2019 were enrolled. We evaluated hemodynamics with right heart catheterization, arterial blood gas examination, New York Heart Association functional class (NYHA-FC), respiratory function tests, nocturnal oximetry, and exercise capacity (6-min walk test and cardiopulmonary exercise testing) at baseline and after BPA. Result: Nearly normal hemodynamics was achieved after BPA (mean pulmonary artery pressure (PAP): 37.5 ± 10.0 to 20.6 ± 4.9 mmHg, p < 0.01). Oxygenation slightly improved (partial pressure of arterial oxygen; 61.5 ± 12.3 to 67.7 ± 12.7 mmHg, p < 0.01). Exertional desaturation remained unchanged (−8.1 ± 4.8 to −7.8 ± 5.1, p = 0.59), and this was associated with residual symptom (NYHA-FC ≥ 2) after BPA (OR 0.591, 95% CI 0.416–0.840, p = 0.003) in multivariate regression analyses. Lower vital capacity (r 2 = 0.03, p = 0.01), higher mean PAP (r 2 = 0.08, p = 0.02), and higher minute ventilation/carbon dioxide production (VE/VCO2 ) slope (r 2 = 0.18, p < 0.01), the marker of ventilatory inefficiency, were correlated with exertional desaturation after BPA in multivariate linear analyses. Conclusion: Although hemodynamics nearly normalized, oxygenation did not. Moreover, exertional desaturation remained unchanged. This might cause residual symptom after BPA. Residual pulmonary hypertension suggesting incurable arteriopathy, and higher VE/VCO2 slope suggesting ventilation-perfusion mismatch might be related to exertional desaturation. Domiciliary oxygen therapy should be continued, if necessary. Highlights: Oxygenation remained impaired, and exertional or nocturnal desaturation remained unchanged after BPA. Sustained desaturation was associated with residual symptoms despite nearly normalized hemodynamics after BPA. Sustained desaturation was associated with residual symptoms despite nearly normalized hemodynamics after BPA.